Los Olivos: Un distrito hacia la prosperidad - Lázaro Aranda, Isabel (2008)
To improve the living conditions of the population or to diminish the poverty, it is a complex and polemic topic, from its definition and measurement up to the design of social policies and strategies to overcome it. The principal aim of the present article is evaluates the standard of living of the population of the district “Los Olivos”, on the base of the behavior of a set of partial indicators, from a socioeconomic, ecological perspective and of civil safety. Los Olivos is located in the Cone North of Metropolitan Lima, whose population stands at 318140 inhabitants; of which, 51.6 % are women (Census 2007) . The population of Los Olivos , has access to basic services of housing, lives in acceptable conditions of health and without overcrowding. The majority of the population is alfabeta (93%); show high rates of schooling at the following levels of basic education regulate: Primary 6 to 11 years of age (81%) and secondary 12 to 16 years of age (80%). The assistance to the educational institutions is massive (98.6 %) and homogeneous in all the normative ages with a confidence probability of 95 %. The Economically Active Population (EAP) is estimated in 94933 persons who represent 46.5 % of the Population in Age of Working (of 14 years and more). With regard to the EAP, 92.5 % are employed; being observed a rate of unemployment opened of only 7.5 %, below the average level of Metropolitan Lima. Nevertheless, this district lacks advance in the solution of the problems of the inequality in the distribution of the income and of the civil safety.